Transient response of pretwisted delaminated stiffened shell under low velocity impact. Issue 3 (4th May 2018) - Rout, Mrutyunjay; Hota, Sasank Shekhar; Karmakar, Amit
ABSTRACT: The paper presents the study of low velocity impact response of delaminated composite stiffened shell with pretwist employing finite element method for different combination of stiffeners. An eight noded isoparametric shell element along with a three noded isoparametric beam element are employed to model the shell and the stiffener, respectively. The modified Hertzian contact law is considered to compute the contact force, while the Newmark's time integration algorithm is used to solve the time dependent equations of both impactor and shell. The multipoint constraint algorithm is used to model delamination. Finally, the parametric studies are reported.